1999
DOI: 10.1086/301042
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Populations at the Center of IC 1613

Abstract: We have observed the center of the Local Group dwarf irregular galaxy IC 1613 with WFPC2 aboard the Hubble Space Telescope in the F439W, F555W, and F814W filters. We find a dominant old stellar population (aged ~7 Gyr), identifiable by the strong red giant branch (RGB) and red clump populations. From the (V-I) color of the RGB, we estimate a mean metallicity of the intermediate-age stellar population [Fe/H] = -1.38 +/- 0.31. We confirm a distance of 715 +/- 40 kpc using the I-magnitude of the RGB tip. The main… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 63 publications
7
82
2
Order By: Relevance
“…sites of young star formation characterise the majority of the transition-type dwarfs in the Sculptor group (Jerjen & Rejkuba 2001;Lianou et al 2012), while the same is also observed for the young stellar populations of other LG dwarf galaxies (e.g, Dohm-Palmer et al 1997;Gallagher et al 1998;Mateo 1998;Cole et al 1999;McConnachie et al 2006). …”
Section: Colour−magnitude Diagram and Stellar Contentmentioning
confidence: 70%
“…sites of young star formation characterise the majority of the transition-type dwarfs in the Sculptor group (Jerjen & Rejkuba 2001;Lianou et al 2012), while the same is also observed for the young stellar populations of other LG dwarf galaxies (e.g, Dohm-Palmer et al 1997;Gallagher et al 1998;Mateo 1998;Cole et al 1999;McConnachie et al 2006). …”
Section: Colour−magnitude Diagram and Stellar Contentmentioning
confidence: 70%
“…The global metallicity of [Fe/H] = −1.23 ± 0.06 for IC 1613 was estimated from the relation between the C/M ratio and metallicity developed by Cioni (2009). This metallicity value is not much different from the previous results for the metallicity of IC 1613 (Freedman 1988;Cole et al 1999;Zucker & Wyder 2004). More recently, Sibbons et al (2015) also derived the metallicity of [Fe/H] = −1.26±0.07 for IC 1613 from their C/M ratio.…”
Section: Spatial Distributions Of the C And M-giant Stars C/m Ratiomentioning
confidence: 88%
“…Several studies with optical data have provided a low-extinction value of E(B − V) = 0.02 ∼ 0.04 (Sandage 1971;Freedman 1988;Cole et al 1999) for IC 1613. The map of Schlegel et al (1998), based on the dust infrared emission feature of the COBE and IRAS data, gives the reddening value of E(B − V) = 0.03 for IC 1613.…”
Section: Photometric Properties Of the Agb Stars In Ic 1613mentioning
confidence: 99%
See 2 more Smart Citations